A Study On Green Business Efficiency and Its Challenges - Gowri, Gowri; Maheswari, G.S.; Kavitha, M. (Journal of Neonatal Surgery, 2025)
Environmentally aware consumers can, again, act either individually or collectively. The individual green behavior manifests itself in personal decisions whether to act in a green way (e.g., recycle) and to pay more for a green product, or not. Green businesses may be eligible for government incentives, such as tax breaks or grants. It also ensures that their products and services don't become obsolete in the global push for sustainability.Finally, it concludes that, Consumers are increasingly willing to support green businesses that are good for the environment.